Treatment with glucagon‐like peptide‐1 receptor agonists and incidence of dementia: Data from pooled double‐blind randomized controlled trials and nationwide disease and prescription registers - Caroline Holm Nørgaard; Sarah Friedrich; Charlotte Thim Hansen; Thomas Gerds; Clive Ballard; Daniel Vega Møller; Lotte Bjerre Knudsen; Kajsa Kvist; Bernard Zinman; Ellen Holm; Christian Torp‐Pedersen; Lina Steinrud Mørch (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction People with type 2 diabetes have increased risk of dementia. Glucagon‐like peptide‐1 (GLP‐1) receptor agonists (RAs) are among the promising therapies for repurposing as a treatment for Alzheimer's disease; a key unanswered question is whether they reduce dementia incidence in people with type 2 diabetes. Methods We assessed exposure to GLP‐1 RAs in patients with type 2 diabetes and subsequent diagnosis of dementia in two large data sources with long‐term follow‐up: pooled data from three randomized double‐blind placebo‐controlled cardiovascular outcome trials (15,820 patients) and a nationwide Danish registry‐based cohort (120,054 patients). Results Dementia rate was lower both in patients randomized to GLP‐1 RAs versus placebo (hazard ratio [HR]: 0.47 (95% confidence interval [CI]: 0.25–0.86) and in the nationwide cohort (HR: 0.89; 95% CI: 0.86–0.93 with yearly increased exposure to GLP‐1 RAs). Discussion Treatment with GLP‐1 RAs may provide a new opportunity to reduce the incidence of dementia in patients with type 2 diabetes.